(3JaSjQ GdbQBfs - (3Ydj Hf EHQGgje Hf gGTe Gdobqej, CHh GdMSf , cGf MkqjG bHd (B329 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdCMO GdeJaQO GdUeO GdPi dG ef TF cGf hdG ef TF Ndb eG jchf s
(3BNQgG (B:s
(3heG cGf ef PcQ GdGSe hGdaQhb hGdYPGH fRd HecI Je hGdMeO dg Mb MeOg dGjSJWjY YHO Cf jbhd dh cGf gPG GfRdg ai GdbQBf hbO GfRdg Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3O MSjf Ydi eMahX (B(81) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs